Math, asked by minion217, 1 year ago

please tell this one..sum upto n terms...​

Attachments:

Answers

Answered by IamIronMan0
0

Answer:

Let

s = 1 + 3x + 5 {x}^{2}  + 7 {x}^{3} ..... \\ xs =  \:  \: \:  \:  \:  \:   \:   x  \: + 3 {x}^{2}  + 5 {x}^{3} .... \\  -  -  -  -  -  -  -  -  -  -  -  -  -  -  \\ (1 - x)s = 1 + 2x + 2 {x}^{2}  + .... \\ (1 - x)s = 1 + 2(x +  {x}^{2}  + ....) \\ \\  (1 - x)s = 1 +  \frac{2x}{1 - x}  \\  \\ s =  \frac{1}{1 - x}  +  \frac{2x}{(1 - x) {}^{2} }

Similar questions